Vagal Nerve Stimulation in the Treatment of Olanzapine Related Super Refractory Status Epilepticus: A Case Report - Demet İLHAN ALGIN; Hasan ÇAĞLAR; Özlem AYKAÇ; Murat VURAL; Oğuz Osman ERDİNÇ (Archives of Epilepsy, 2020)

(untitled)
Olanzapine-related seizures have rarely been reported despite associated proconvulsant risk factors described in the literature. Refractory and super refractory status epilepticus is continuous seizure activity not controlled by antiepileptic drugs and related poor outcomes. Because of high mortality with polypharmacy and continuous anesthetic use, there has been a considerable interest in using nonmedicinal devices like vagal nerve stimulation in aborting a seizure. In this case study, we presented a patient who developed generalized tonic-clonic seizures when olanzapine was added for psychomotor agitation and aggressiveness and super refractory status epilepticus treated using vagal nerve stimulation.